A Review on Pacemakers: Device Types, Operating Modes and Pacing Pulses. Problems Related to the Pacing Pulses Detection - Valentin Tsibulko; Ivo Iliev; Irena Jekova (International Journal Bioautomation, 2014)
A pacemaker is a small battery-operated medical device that delivers electrical impulses to the heart in order to guarantee regular contractions. Depending on the number of active leads the pacemakers are single chamber, dual chamber and bi-ventricular. According to their programming the devices could be with fixed-rate, 'on demand' and rate-responsitive. The operating mode of the pacemaker depends on the paced chamber, the sensed chamber, the response to a sensed electrical signal and the rate modulation. Two types of pacing are recognized - unipolar and bipolar, represented with different pacing artifacts in the ECG signal. The pacing pulse on the skin surface usually have very fast rising edges of the order of 10 µs or less and could be as small as few hundreds µV. The pacing artifacts detection is important since they indicate the presence of a pacemaker and help to evaluate the reaction of the heart. All pertinent medical standards require the pacing artifacts to be captured and indicated on the screen of the device. This paper presents a short review on pacemakers - reasons for implementation, device types, different operation modes and pacing pulses. It reveals some common problems with the detection of pacemaker's artifacts.